Children hospitalized for juvenile arthritis in the United States - Nomesh Kumar (Termedia Publishing House, 2021)
Juvenile arthritis (JA) is an autoimmune condition affecting children. We used the 2017 National Inpatient Sample (NIS) to evaluate the impact of JA in the United States. The admission data were converted to weighted form and patients between the ages of 0 and 18 (inclusive) were used in our study. 560 weighted cases were found in 2017. It was more common in females than males (340 females, 220 males), Whites (235 cases), and Medicaid covered 61.6% of all patients with JA (345 cases). The total hospital charges were $25,147,389 while the mean length of stay (LOS) was 4.55 days. The highest number of cases was reported in April 2017.